Systematic scoping review of the concept of 'genetic identity' and its relevance for germline modification. - Floor M Goekoop; Carla G van El; Guy A M Widdershoven; Nadza Dzinalija; Martina C Cornel; Natalie Evans (PLoS ONE, 2020)
EU legislation prohibits clinical trials that modify germ line 'genetic identity'. 'Genetic identity' however, is left undefined. This study aims to identify the use of the term 'genetic identity' in academic literature, and investigate its relevance for debates on genetic modification. A total of 616 articles that contained the term were identified. Content analysis revealed that the term was used in various and contradicting ways and a clear understanding of the term is lacking. This review demonstrates that the EU legislation is open to interpretation, because of the diversity of meaning with which 'genetic identity' is currently used. Because of the diversity of meaning with which 'genetic identity' is used and understood, further reflection is needed. This requires further medical, legal, ethical and social debate and a coordinated response at both a European and a global level.